2006
DOI: 10.1212/01.wnl.0000240130.94408.99
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometry shows no decreases in cerebellar gray matter volume in essential tremor

Abstract: The lack of a consistent decrease in gray and white matter density argues against a progressive neurodegenerative process in essential tremor that leads to a substantial decrease in cerebellar gray matter volume. Patients with predominant intention tremor show a relative expansion of gray matter areas involved in higher order visuospatial processing, which might represent a long-term result of adaptive reorganization compensating the higher demands on the visuospatial control of skilled movements in case of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
97
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 54 publications
(57 reference statements)
18
97
2
Order By: Relevance
“…These differences are not expected to have confounded our findings since no morphological correlates of either balance impairment or motor fluctuations and dyskinesias were identified in additional VBM analyses, motor fluctuations and dyskinesias presumably originate from long-lasting functional alterations without known structural abnormality, and impaired balance and eventually loss of postural stability in PD is primarily caused by degeneration of brainstem nuclei such as the tegmental pedunculopontine nucleus [45,52,57]. Essential tremor which could be a confounding factor, even though a recent VBM study had failed to detect cerebellar changes in essential tremor [14], was clinically excluded. Postural and action tremor related to PD differs from essential tremor and is considered a continuation of rest tremor during action and posture presumably originating from the same tremor generator [37].…”
Section: Discussionmentioning
confidence: 99%
“…These differences are not expected to have confounded our findings since no morphological correlates of either balance impairment or motor fluctuations and dyskinesias were identified in additional VBM analyses, motor fluctuations and dyskinesias presumably originate from long-lasting functional alterations without known structural abnormality, and impaired balance and eventually loss of postural stability in PD is primarily caused by degeneration of brainstem nuclei such as the tegmental pedunculopontine nucleus [45,52,57]. Essential tremor which could be a confounding factor, even though a recent VBM study had failed to detect cerebellar changes in essential tremor [14], was clinically excluded. Postural and action tremor related to PD differs from essential tremor and is considered a continuation of rest tremor during action and posture presumably originating from the same tremor generator [37].…”
Section: Discussionmentioning
confidence: 99%
“…3 On the other hand, a recent voxel-based morphometry (VBM) study failed to find gray or white matter abnormalities in the cerebellum of patients with intentional or postural ET, which raises doubt about the role that the cerebellum plays in ET. 4 However, recent neuropathologic studies in patients with ET have demonstrated brain stem Lewy bodies in some patients and cerebellar pathology in others, further supporting the evidence that the cerebellum is of importance for the pathophysiology of this disease. 5,6 The most recognized clinical feature of ET is a kinetic and postural tremor of the arms.…”
mentioning
confidence: 86%
“…34,35 Taken at face value, these reports suggest a generalized effect of ET on the cerebellothalamocortical network, 34,35 but these positive results are not ubiquitous in the literature. 36 The lack of definitive macroscopic markers for cerebellar atrophy 36 and ET-specific morphologic changes reflect the ambiguous picture that currently describes pathology at the microscopic level. Some questions regarding ET pathology could be explored with existing tools.…”
Section: The Need For Neuroimaging Markers As a Diagnostic Tool For Etmentioning
confidence: 99%
“…Whole-brain analysis, on the other hand, allows exploration of widespread networks but may not be specific enough, with the risk of ignoring smaller regions and nuclei. 41 The data that make up all of the neuroimaging descriptions of ET were acquired at different magnet field strengths (most at 1.5T 32,33,36,40,46 and 3T 34,35,41,42,44 ). Accordingly, contrast and resolution, the parameters that, for the most part, guide the interpretation and analysis of the images, cannot be assumed constant.…”
Section: Potential Bias In Et Neuroimaging Studiesmentioning
confidence: 99%